Managing public floors in private development: perceptions and challenges - Max, David; Mualam, Nir (Property management, 2025)
PurposeThis paper examines the phenomenon of mixing public floors within private development, shedding light on underlying rationales, the acceptability of integrating different uses, and the various challenges associated with the management and creation of these mixed-use, mixed-ownership buildings.Design/methodology/approachThe topic is reviewed by examining the opinions and perceptions of expert planners and developers using a triangulation of qualitative interviews data and quantitative and qualitative analysis of survey results, cross-referenced with some grey literature in the form of planning tribunal decisions.FindingsFindings suggest that the allocation of public floors is made in response to the shortage of land in high-demand areas with the aim of densifying development and making it more efficient. Experts were generally open to the concept of a private–public floorspace mix, noting that certain public land uses are better than others when combined as floorspace within private structures. Furthermore, the findings highlight managerial obstacles as well as issues with the process of allocating public floors in new plans.Practical implicationsThe findings can be used to provide guidance for municipal authorities and developers looking to make the most of their available land, ensuring that both the public and private domains can coexist as cities continue to grow and become more densely populated in the future.Originality/valueFew studies have reviewed this type of public–private mix, while highlighting challenges in their creation and management. The Israeli case-study in the paper showcases a unique context where high growth rates, increasing densification, and vertical development all spur development in this direction.